Cross-linked human serum albumin dimer has the potential for use as a plasma-retaining agent for the fatty acid-conjugated antidiabetic drugs - Taguchi, K.; Chuang, Victor; Yamasaki, K.; Urata, Y.; Tanaka, R.; Anraku, M.; Seo, H.; Kawai, K.; Maruyama, T.; Komatsu, T.; Otagiri, M. (Blackwell Publishing Ltd, 2015)
Objectives The half-life of fatty acid-conjugated antidiabetic drugs are prolonged through binding to albumin, but this may not occur in diabetic patients with nephropathy complicated with hypoalbuminemia. We previously showed that human serum albumin (HSA) dimerized at the protein's Cys34 by 1,6-bis(maleimido)hexane has longer half-life than the monomer under high permeability conditions. The aim of this study was to investigate the superior ability of this HSA dimer as a plasma-retaining agent for fatty acid conjugated antidiabetic drugs. Methods The diabetic nephropathy rat model was prepared by administering a single injection of streptozotocin (STZ) intravenously, and the pharmacokinetic properties of HSA monomer and dimer were evaluated. Site-specific fluorescent probe displacement experiments were performed using warfarin and dansylsarcosine as site I and site II specific fluorescent probes, respectively. Key findings The half-life of the HSA dimer in STZ-induced diabetic nephropathy model rats was 1.5 times longer than the HSA monomer. The fluorescent probe displacement experiment results for HSA monomer and dimer were similar, where fatty acid-conjugated antidiabetic drugs displaced dansylsarcosine but not warfarin in a concentration-dependent manner. Conclusions The HSA dimer shows potential for use as a plasma-retaining agent for antidiabetic drugs due to its favourable pharmacokinetic properties.